2001
DOI: 10.1152/ajplung.2001.280.5.l1049
|View full text |Cite
|
Sign up to set email alerts
|

Dual signaling by the αvβ3-integrin activates cytosolic PLA2in bovine pulmonary artery endothelial cells

Abstract: Vitronectin, which ligates the alpha(v)beta(3)-integrin, increases both lung capillary permeability and lung endothelial Ca(2+). In stable monolayers of bovine pulmonary artery endothelial cells (BPAECs) viewed with confocal microscopy, multimeric vitronectin aggregated the apically located alpha(v)beta(3)-integrin. This caused arachidonate release that was inhibited by pretreating the monolayers with the anti-alpha(v)beta(3) monoclonal antibody (MAb) LM609. No inhibition occurred in the presence of the isotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Several other studies have demonstrated that cPLA 2 activity can be regulated by MAPKs (15,30,58). It has been suggested that p44/ 42MAPK activation and an increase of intracellular calcium are both conjointly required for full cPLA 2 activation and subsequent arachidonate release (8,30). Our observation that inhibition of calcium-dependent cPLA 2 completely abolished the stretch-induced increase in PG content, whereas inhibition of p44/42MAPK only partially reduced stretch-induced PG increases, supports the dual-activation scenario for cPLA 2 .…”
Section: Ajp-lung Cell Mol Physiolmentioning
confidence: 98%
“…Several other studies have demonstrated that cPLA 2 activity can be regulated by MAPKs (15,30,58). It has been suggested that p44/ 42MAPK activation and an increase of intracellular calcium are both conjointly required for full cPLA 2 activation and subsequent arachidonate release (8,30). Our observation that inhibition of calcium-dependent cPLA 2 completely abolished the stretch-induced increase in PG content, whereas inhibition of p44/42MAPK only partially reduced stretch-induced PG increases, supports the dual-activation scenario for cPLA 2 .…”
Section: Ajp-lung Cell Mol Physiolmentioning
confidence: 98%
“…The stimulation of COX-2-dependent PGE 2 production upon ␣ V ␤ 3 -dependent adhesion could result from the ␣ V ␤ 3 -mediated activation of phospholipase A2 (PLA2) and the production of arachidonic acid, the substrate of COX. In this respect, it has been recently reported that ␣ V ␤ 3 ligation induces membrane translocation and activation of PLA2 with the subsequent release of arachidonic acid in bovine pulmonary artery endothelial cells (37). PLA2 appears to be stimulated by integrin ligation in several cell types, and in some cases its activation has been linked to the production of arachidonic acid, the activation of PKC, and cell spreading (38,39).…”
Section: Pgementioning
confidence: 98%
“…As to mechanism for stretch-induced prostanoid synthesis, we initially considered that integrins, a family of cell-adhesion molecules interacting with the extracellular matrix, might interact with the cascade because integrins might be involved in the mechanosensitive architecture of the cell membrane, leading to mechanotransduction in a variety of cells (2). In fact, it has been reported that integrin α v β 3 , an RGDpeptide-sensitive isoform (3), was involved in the vitronectin-induced activation of cytosolic PLA 2 (cPLA 2 ) and arachidonate release in bovine pulmonary artery endothelial cells (4). Since cPLA 2 has a major role in prostanoid production (5), we had assumed that blockade of RGD-sensitive integrin would inhibit the stretchinduced prostanoid production.…”
mentioning
confidence: 99%
“…Integrin-dependent cPLA 2 activity has been reported in several types of cells, for example, β 1 integrin in NIH-3T3 murine fibroblasts (13) and α v β 3 integrin in bovine pulmonary artery endothelial cells (4). In the present study, we considered that sPLA 2 , another type of PLA 2 which is a RGD-peptide-insensitive enzyme due to its secretary nature extracellularly, may play a key role in the enhanced contractility of pulmonary arteries of rabbits because neither the contraction nor the untransformed PGH 2 production was affected by the RGD-integrin blockade (2).…”
mentioning
confidence: 99%